THE KIAI’S MODERATE LEADERSHIP MODEL IN IMPROVING THE QUALITY OF EDUCATIONAL SERVICES - Sari Hernawati (Pascasarjana Universitas Wahid hasyim Semarang, 2015)
This research is basically based on the phenomena that the Kiai (religious leader) has a significant role at the Islamic Boarding Schools (Pesantren). An effective leadership of Kiai will absolutely determine model of changes conducted by Pesantren in improving the quality of education services without removing its Islamic education values. Generally the study is field research and conducted at the Islamic Boarding Schools (Pesantren) Al-Hikmah 2 and As-Salafiyyah Brebes. It uses qualitative approach. Whereas the method of data collection is interview, observation, documentation and triangulation in which the key instrument is the researcher himself. Results of research are: (1) vision of Kiai has a philosophical sense, namely building moderate Islamic character of santri (student) is a worship and devotion to Allah SWT, (2) the strategy of As-Salafiyah Islamic boarding school is to preserve and defend existing salaf (classic) pattern, meanwhile al Hikmah’s strategy is to respond modernity trough development and open some new general education institutions. Keywords: leadership model; kiai; pesantren; education; services quality